2020
DOI: 10.5815/ijcnis.2020.03.01
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed and Secure PRNG for Cryptographic Applications

Abstract: Due to the fundamentally different approach underlying quantum cryptography (QC), it has not only become competitive, but also has significant advantages over traditional cryptography methods. Such significant advantage as theoretical and informational stability is achieved through the use of unique quantum particles and the inviolability of quantum physics postulates, in addition it does not depend on the intruder computational capabilities. However, even with such impressive reliability results, QC methods h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Therefore, the development of new practices and management methods of diverse web projects during crises is an important task. A detailed analysis of all the factors and influences that affect the management of web projects during crises [15,16] will allow us to predict the direction of web service development and the key threats in the process of web project management [17][18][19][20]. There are many different solutions for data discovery and analysis in web projects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of new practices and management methods of diverse web projects during crises is an important task. A detailed analysis of all the factors and influences that affect the management of web projects during crises [15,16] will allow us to predict the direction of web service development and the key threats in the process of web project management [17][18][19][20]. There are many different solutions for data discovery and analysis in web projects.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the analysis of the security and efficiency are taken into the consideration in our research. In paper [2] theoretical and informational stability is achieved through the use of unique quantum particles and the inviolability of quantum physics postulates, in addition, it does not depend on the intruder computational capabilities. Although these quantum cryptography methods have some drawbacks, the authors have developed a reliable trit generation method and software tool to obtain a fast and safe PRNG.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent events have shown that random number generators are especially attractive for secret attacks. For example, the pseudo-random number generation algorithm DUAL_EC_DBRG, proposed as the NIST standard, allows an attacker to retrieve an entire random sequence with minimal information, with practical consequences during Juniper network attack (CVE7755, 2015) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of paper [12] describe a fundamentally different approach using the trit generation method and software tool TriGen v.2.0 PRNG, which has significant advantages over traditional cryptography methods. In [13][14], the authors present a study of high-speed and secure pseudo random number (PRN) generation techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Randomness is the basis for cryptography. The vast majority of PRNGs are incapable of generating cryptographically secure random numbers [12][13][14]. If we have sufficient output values, we can infer the internal state of Mersenne Twister, for example.…”
Section: Optical Quantum Random Number Generatorsmentioning
confidence: 99%